(untitled) (Research, Society and Development, 2023)
Objective: identification of strategies inherent to the prevention and mitigation of cases of obstetric violence in the country. Methods: integrative review, based on the examination of scientific productions published in the last ten years, contemplating the following languages: Portuguese, English and Spanish, selected in the academic platforms LILACS and SCIELO. Results: 15 scientific productions with a publication date between 2013 and 2023 were reviewed. The following were identified as the main preventive and reducing measures against obstetric violence: interference in the training and qualification of health professionals; actions to inform and strengthen women’s autonomy and rights; participatory health management qualification; humanization of childbirth; construction of the birth plan, recommended by the World Health Organization (WHO); observance of the right to a companion; role of obstetric nursing; construction of Normal Birth Centers (BC); social awareness and use of information technologies; support from women’s movements; development of research and data on obstetric violence; promotion of the visibility and accountability of those involved and regulation of the institute, through federal legislation.Conclusion: The joint engagement between society and government is essential to reduce cases of obstetric violence at the national level, through different strategies to be implemented, in the fight against resistance positions, which reinforce the invisibility of the theme. The need to break with obstetric violence is based on the construction of a holistic model of childbirth care, guided by woman-centered care, safe and free from any behaviors that take away the beauty of experiencing motherhood.